Preventif TB Paru Melalui Pengobatan, Informasi dan Edukasi Kepada Masyarakat di Wilayah Kerja Puskesmas Rejosari - Alamsyah, Agus; Oktavia, Juwita; Jumailina Rista, Tessy; Hidayahti, Tika (Jurnal Pengabdian Kesehatan Komunitas (Journal of Community Health Service), 2021)
Tuberculosis is an infectious disease caused by germs Mycobacterium tuberculosis. There are several species Mycobacterium, among others : M. tuberculosis, M. africanum, M.bovis, M. Laprae dsb. Which is also known as acid resistant bacteria (BTA). Mycobacterium group other than Mycobacterium tuberculosis which can cause distruption of the airways known as MOTT (Mycobacterium Other Than Tuberculosis) which sometime can interfere with the diagnosis of TBC treatment. PKM’s aim is to increase peoples’s knowledge with information and education to the public as a preventive measure against TBC. Methods of health counseling education about TB prevention through information and education to the public. Target community PKM is people in working area Puskesmas Rejosari Tenayan Raya sub-district, Pekanbaru city. The activity was carried out on 12 December 2019. The results of the PKM activity found that out of 25 people participating in the activity, 80% of the community knew about TBc disease and 70% understood how to prevent and treat TBC. It is recommended the puskesmas rejo sari especially the part promkes to intensify provide education and information related to TB disease and the way prevented TB disease also can be eradikasi.